2004
DOI: 10.1097/01.wad.0000126617.54783.7
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of Chinese Frontal Assessment Battery in Evaluating Executive Dysfunction Among Chinese Patients With Small Subcortical Infarct

Abstract: Although CFAB is reliable, it is only moderately valid in evaluating executive dysfunction among Chinese stroke patients with small subcortical infarct. The clinical use of CFAB in the evaluation of executive dysfunction among this group of patients cannot be recommended at this stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 30 publications
5
42
1
Order By: Relevance
“…Existing validation studies observed cutoffs of 11/12 for executive dysfunction in subcortical infarct (Sn: 69.2%, Sp: 87.7%, Ac: 80.6%) [9] and differentiated AD (cutoff 11/12; Sn: 77%, Sp: 87%) [2] from frontotemporal dementia (cutoff 10/11; Sn: 85–92%, Sp: 85%) [8]. The cutoff scores in our study are more similar to the normative values in an Italian population control sample [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Existing validation studies observed cutoffs of 11/12 for executive dysfunction in subcortical infarct (Sn: 69.2%, Sp: 87.7%, Ac: 80.6%) [9] and differentiated AD (cutoff 11/12; Sn: 77%, Sp: 87%) [2] from frontotemporal dementia (cutoff 10/11; Sn: 85–92%, Sp: 85%) [8]. The cutoff scores in our study are more similar to the normative values in an Italian population control sample [15].…”
Section: Discussionmentioning
confidence: 99%
“…Depression was assessed via the Cornell Scale for Depression in Dementia [24]. The Chinese FAB was administered to the subjects [9] during the initial visit by a single blinded rater. The Chinese FAB consists of 6 subtests: (1) conceptualization (conceptualization links between 2 objects from the same category, e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Corroborating evidence comes from the validation study of the Chinese Frontal Assessment Battery, where it was reported that normal controls consistently scored lower on the similarities item (mean=0.71) compared with the other five items, including the differences item (range of means: 2.5-3.0). 84 Not uncommonly, the protectiveness towards the elderly seen in many conservative Asian families, often encourages a longstanding restricted and homebound lifestyle with little variability in their daily routines and where most tasks are taken over by their families. 5,13 In such circumstances, the utility of testing recent autobiographical memory (which involves the recall of recent events in the last 1 week and 1 month) would be limited.…”
Section: Influence Of Culture On Cdr Scoringmentioning
confidence: 99%